Characterization of Photovoltaic Panels by means of Thermograph Analysis - Noe Samano; José Alfredo Padilla-Medina; Nimrod Vázquez (International Journal of Photoenergy)
Solar panels have become attractive in order to generate and supply electricity in commercial and residential applications. Their increased module efficiencies have caused not only a massive production but also a sensible drop on sale prices. Methods of characterization, instrumentation for in situ measurements, defect monitoring, process control, and performance are required. A temperature characterization method by means of thermograph analysis is exposed in this paper. The method was applied to multicrystalline modules, and the characterization was made with respect to two different variables, first a thermal transient and second a characterization with respect to the current. The method is useful in order to detect hot spots caused by mismatch conditions in electrical parameters. The description, results, and limitations of the proposed method are discussed.